SUR1 regulates PKA-independent cAMP-induced granule priming in mouse pancreatic B-cells. - Eliasson, L; Ma, X; Renström, E; Barg, S; Berggren, P; Galvanovskis, J; Gromada, J; Jing, X; Lundquist, I; Salehi, A; Sewing, S; Rorsman, P (2003)
Measurements of membrane capacitance were applied to dissect the cellular mechanisms underlying PKA-dependent and -independent stimulation of insulin secretion by cyclic AMP. Whereas the PKA-independent (Rp-cAMPS-insensitive) component correlated with a rapid increase in membrane capacitance of approximately 80 fF that plateaued within approximately 200 ms, the PKA-dependent component became prominent during depolarizations >450 ms. The PKA-dependent and -independent components of cAMP-stimulated exocytosis differed with regard to cAMP concentration dependence; the K(d) values were 6 and 29 micro M for the PKA-dependent and -independent mechanisms, respectively. The ability of cAMP to elicit exocytosis independently of PKA activation was mimicked by the selective cAMP-GEFII agonist 8CPT-2Me-cAMP. Moreover, treatment of B-cells with antisense oligodeoxynucleotides against cAMP-GEFII resulted in partial (50%) suppression of PKA-independent exocytosis. Surprisingly, B-cells in islets isolated from SUR1-deficient mice (SUR1(-/-) mice) lacked the PKA-independent component of exocytosis. Measurements of insulin release in response to GLP-1 stimulation in isolated islets from SUR1(-/-) mice confirmed the complete loss of the PKA-independent component. This was not attributable to a reduced capacity of GLP-1 to elevate intracellular cAMP but instead associated with the inability of cAMP to stimulate influx of Cl(-) into the granules, a step important for granule priming. We conclude that the role of SUR1 in the B cell extends beyond being a subunit of the plasma membrane K(ATP)-channel and that it also plays an unexpected but important role in the cAMP-dependent regulation of Ca(2+)-induced exocytosis.